(3eYQaI ChbGJ GdUdGI hLgI GdbHdI ef QHY GdebfWQGJs - (3ehSi Hf eMeO Hf YKeGf GdNdjdjs
(3ChdgG (B:s
(3bGd GdQSGdI GdKGefI (B: (3ai eYQaI ChbGJ GdUdGI hPdc ai SfI aUhd (B: (3GdaUd GdChd ai eYQaI QShe QHY GdebfWQGJ s
(3BNQgG (B:s
(3Ke jYjf GdNW Ydi Pdc GdecGf Ke jWhd Pdc GdNW Ydi GSJbGeJg Edi GdehVhY GdeWdhH hcPdc jaYd HNW GdbHdI hGddg CYde JeJ HMeO Gddg s
(3Vef eLehY , JQJjHgG (B: (3ef U (B136 - (3U(B146s
(3HgG fXGe GdJYbjHIs
(3cJHJ Hbde ajg VHWs
(3GdJhKjbGJ GdeQLYjI (B:s
(3HQhcdeGf (B- (3GdLRA (B2 - (3U (B157 ; (3HQhcdeGf edMb (B- (3GdLRA (B2 - (3U (B158 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA (B3 - (3bSe (B2 s
(3eUOQ GbJfGA GdCUd (B:s
(3GdaGJjcGf (B(494) s
Keywords: (3Gdadcs